2014
DOI: 10.4028/www.scientific.net/amr.1082.270
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pile Joints

Abstract: Opportunities of factories, transport companies and piling driving machines does not allow to produce longer piles when it is necessary. Currently this problem could be solved by joining parts of piles. A wide range of pile joints are known therefore it is a problem for building companies to choose which one is more relevant. In this connection there is a need to identify what joint is the most optimal. In this work main types of joints are compared in accordance with up-to-date requirements to building constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It could be seen that full welding of end plates and long pins strengthened the continuity of pipe pile joints, which effectively transferred the joint forces to the pile concrete and made its bending strength close to that of the pile material. In particular, the pin type mechanical joint was also a proven efficient connection method [49]. It must be stated that although the above joint strengthening measures are difficult to fully achieve in engineering practice, the joint connection structure can be optimized to enhance the bending strength by using Rachel reinforcement connection implanted into concrete, filling highstrength structural bar glue between end plates, and adding ribs on the inner wall of the pile hoop.…”
Section: Joint Connection Modementioning
confidence: 99%
“…It could be seen that full welding of end plates and long pins strengthened the continuity of pipe pile joints, which effectively transferred the joint forces to the pile concrete and made its bending strength close to that of the pile material. In particular, the pin type mechanical joint was also a proven efficient connection method [49]. It must be stated that although the above joint strengthening measures are difficult to fully achieve in engineering practice, the joint connection structure can be optimized to enhance the bending strength by using Rachel reinforcement connection implanted into concrete, filling highstrength structural bar glue between end plates, and adding ribs on the inner wall of the pile hoop.…”
Section: Joint Connection Modementioning
confidence: 99%
“…Te experimental results showed that the ultimate antibending capacity of connection joint was greater than that of pile shaft. Several widely used connection methods for precast concrete piles from economic beneft, service life, and feld workload were summarized and compared by Ptuhina et al [23]. Te infuence of topographic and geological conditions was considered by Song et al [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%